2015
DOI: 10.1371/journal.pone.0129765
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Analytical Approach Reveals Potential Microbial Indicators in Soil for Sugarcane Model Systems

Abstract: This study focused on the effects of organic and inorganic amendments and straw retention on the microbial biomass (MB) and taxonomic groups of bacteria in sugarcane-cultivated soils in a greenhouse mesocosm experiment monitored for gas emissions and chemical factors. The experiment consisted of combinations of synthetic nitrogen (N), vinasse (V; a liquid waste from ethanol production), and sugarcane-straw blankets. Increases in CO2-C and N2O-N emissions were identified shortly after the addition of both N and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(81 citation statements)
references
References 56 publications
4
73
0
4
Order By: Relevance
“…This cascade is further reinforced by N fertilization, especially when N is applied with a rich carbon source, such as vinasse (Di et al., ). Previous studies of sugarcane fields have shown that high N 2 O fluxes occur immediately after N fertilization (Carmo et al., ; Navarrete et al., ; Pitombo et al., ; Soares et al., , ). However, denitrification appears to be less important than AOB for N 2 O emissions under our experimental field conditions.…”
Section: Discussionmentioning
confidence: 97%
“…This cascade is further reinforced by N fertilization, especially when N is applied with a rich carbon source, such as vinasse (Di et al., ). Previous studies of sugarcane fields have shown that high N 2 O fluxes occur immediately after N fertilization (Carmo et al., ; Navarrete et al., ; Pitombo et al., ; Soares et al., , ). However, denitrification appears to be less important than AOB for N 2 O emissions under our experimental field conditions.…”
Section: Discussionmentioning
confidence: 97%
“…The samples were taken all in the morning around 10:00 h, and the time in between the samplings were as follows: the first 16 samplings were taken using an interval of ~7 days, after that, 3 samplings used an interval of ~10 days, and the following 2 samplings used an interval of ~15 days with the last one taken using an interval of ~30 days. N 2 O and CO 2 were determined using gas chromatography (SRI 8610 C Model, Torrance, CA, USA) configured with the same analytical conditions as described elsewhere65 (HayeSep-D and N- packed columns at 81 °C). Average of concentrations was calculated as follows: the values of concentrations measured along the experiment were summed and divided by the number of samplings (Figs 2a and 3a).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, there have been efforts to characterize the microbial groups responsible for the soil activities under various management practices in sugarcane cropping areas (Navarrete et al ., ; Pitombo et al ., ; Rachid et al ., ). Rachid et al .…”
Section: Impacts Of Straw Removal On Soil Biological Attributesmentioning
confidence: 97%